Intestinal permeability in patients with Crohn's disease and their first degree relatives. Issue 3 (March 1992) - Teahon, K; Smethurst, P; Levi, A J; Menzies, I S; Bjarnason, I
Abstract : It has been reported that intestinal permeability to polyethylene glycol 400 is increased in patients with Crohn's disease and their apparently unaffected first degree relatives. Because of the implications that these findings have for the aetiology of Crohn's disease these studies were repeated. Patients with Crohn's disease (n = 28) and 32 first degree relatives from 11 families underwent a polyethylene glycol 400 (PEG400) intestinal permeability test and a hyperosmotic (1500 mosmol/l) absorption/permeability test using 3-0-methyl-D-glucose, D-xylose, L-rhamnose, lactulose, and 51chromium labelled ethylenediamine-tetraacetate. The five hour urine excretion of polyethylene glycol 400 did not differ significantly between controls (n = 25) and first degree relatives, 25.5 (3.3)% v 24.6% (4)% (mean(SD)) p greater than 0.1, respectively. Patients with small bowel involvement excreted significantly less (p less than 0.01) polyethylene glycol 400 (16.3 (4.6)% than controls while those with Crohn's colitis did not (26.4 (3.9)% p greater than 0.1). The permeation of the monosaccharides in patients with Crohn's disease and their first degree relatives did not differ from normal subjects. The permeation of lactulose and 51chromium ethylenediaminetetraacetate was not significantly altered in first degree relatives but was significantly increased in the patients, as was the lactulose/L-rhamnose urine excretion ratio which is a specific measure of small intestinal permeability. These studies show normal absorption and permeability in first degree relatives of patients with Crohn's disease. A genetically determined abnormality of intestinal permeability is not likely to be an important aetiological factor in Crohn's disease.